Pengaruh Organization Citizenship Behavior dan Kepuasan Kerja Terhadap Turnover Intention - Mila Hariani (Forum Kerjasama Pendidikan Tinggi, 2022)
In this era, companies are competing to maintain their existence from existing threats. One of the threats to the company is turnover intention. This study aims to determine the effect of organizational citizenship behavior (OCB) and job satisfaction on turnover intention. The population in this study were all employees of a company in Surabaya, namely 107 employees. Sampling in this study used the census technique. The analytical method used is the Linear Regression test with the help of SPSS software. This study shows that organizational citizenship behavior and Job satisfaction has a significant effect on turnover intention. Both variables simultaneously affect turnover intention